Combination of SF1126 and gefitinib induces apoptosis of triple-negative breast cancer cells through the PI3K/AKT–mTOR pathway. Issue 4 (April 2015) - Deng, Miao; Wang, Jianguang; Chen, Yanbin; Zhang, Like; Liu, Dechun
Abstract : To investigate the apoptotic mechanism of triple-negative breast cancer (TNBC) cells induced by gefitinib and PI3K inhibitor SF1126. MDA-MB-231, MDA-MB-436, and MCF-7 cells were incubated with 0.1 μmol/l gefitinib, 1 μmol/l gefitinib, 10 μmol/l gefitinib, 1 μmol/l SF1126, 0.1 μmol/l gefitinib+1 μmol/l SF1126, 1 μmol/l gefitinib+1 μmol/l SF1126, and 10 μmol/l gefitinib+1 μmol/l SF1126. Then, cell viability and survival were determined using an 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyltetrazolium bromide (MTT) assay and Hoechst staining. The apoptosis-related factors and phosphoinositide-3-kinase/protein kinase B, the mammalian target of rapamycin (PI3K/AKT–mTOR) signaling pathway-related factors were detected by western blot. For TNBC cells, cell viability or survival was not significantly inhibited by gefitinib or SF1126 alone; however, marked cell apoptosis was noted in the gefitinib and SF1126 combination groups, and this effect was dose dependent. Also, the expressions of apoptosis markers, such as cleaved caspase-3, Bcl-2/Bax, were altered by the gefitinib and SF1126 combination. Moreover, phosphorylated AKT (p-AKT) and 70 kDa ribosomal protein S6-kinase (p-p70S6K) were also inhibited by the gefitinib and SF1126 combination, which may be responsible for the apoptosis. Gefitinib combined with SF1126 could induce cell apoptosis in TNBC cells and this effect was mediated through the EGFR-PI3K-AKT-mTOR-p70S6K pathway. Our studies have set the stage for future clinical trials of TNBC therapy by the combination of gefitinib and SF1126. Abstract : Supplemental Digital Content is available in the text.